KEUNGGULAN KOMPETITIF SETELAH PANDEMI: STRATEGI REFORMULASI - Pratami Wulan Tresna; Nurillah Jamil Achmawati Novel (JURNAL LENTERA BISNIS, 2024)
This research focuses on MSMEs in Indonesia facing the challenges of the COVID-19 pandemic, with the aim of reformulating post-pandemic competitive advantage strategies. The Systematic Literature Review method was used to collect and evaluate relevant literature. The results showed several key findings: MSMEs must utilize resources to explore new opportunities and manage enterprise growth. About 70% of participants emphasized the importance of online sales and distribution channels to meet changing customer demands. Active and transparent negotiations with stakeholders, including employers, investors and labor, were considered crucial. Proactive and creative leadership is also required to implement effective strategies. In addition, pentahelix cooperation between government, business, academia, society and the media is considered important. The research concluded that MSMEs need to adapt to the changes in habits, behaviors, and technology that occurred during the pandemic to reformulate their vision, mission, goals, and business plans. Controlled and well-monitored strategy implementation is key to achieving competitive advantage in the post-pandemic era.